X-ray fluorescence spectrometry for environmental analysis: Basic principles, instrumentation, applications and recent trends. (September 2022) - Marguí, E.; Queralt, I.; de Almeida, E.
Abstract: In recent years, the conceptual advancement on green analytical chemistry (GAC) has moved in parallel with efforts to incorporate new screening or quantitative low-cost analytical tools to solve analytical problems. In this sense, the role of solid state techniques that allow the non-invasive analysis (or with a minimum sample treatment) of solid samples cannot be neglected. This review describes the basic principles, instrumentation and advances in the application of X-ray fluorescence instrumentation to the environmental sciences research topics, published between 2006 and 2020. Obviously, and because of the enormous number of works that can be found in the literature, it is not possible to exhaustively cover all published articles and the diversity of topics related to the environment in which a solid state technique like XRF has been applied successfully. It is a question of making a compilation of the instrumentation in use, the significant advances in XRF spectrometry and sample treatment strategies to highlight the potential of its implementation for environmental assessment. Graphical abstract: Image 1 Highlights: Analytical applications of X-Ray Fluorescence in the environmental field. Summary of significance advances in XRF systems and sample treatment strategies. Study cases: geological, vegetal, aerosols, aqueous extracts, waters and wastes.